A survey of East Palaearctic Lycosidae (Araneae). 10. Three new Pardosa species from the mountains of Central Asia - Marusik, Yuri M.; Nadolny, Anton A.; Omelko, Mikhail M. (Zootaxa, 2013)
Three new species of Pardosa, P. svatoni sp. n. (♂♀, SE Kazakhstan), P. fengi sp. n. (♂♀, Central Xinjiang) and P. lii sp. n. (♂♀, Central Xinjiang) are described and illustrated. The two former species cannot be placed in any species group. Pardosa lii sp. n. belongs to the P. wagleri species group. It is compared with P. italica Tongiorgi, 1966, whose embolic division has not previously been illustrated.